The Effectiveness of Social Media Use Shapes the Satisfaction in Digital Business - Bayti, Nur; Sihombing, Brylyan Raymundo; Firdiyansyah, Indra (Jurnal Informatika Ekonomi Bisnis, 2025)
The objective of this study is to investigate the effectiveness of social media influence the satisfaction to assess the extent to which students at the Faculty of Economics and Maritime Business, Raja Ali Haji Maritime University (FEBM UMRAH), in running a digital business. The rapid digital transformation and development of social media have created new entrepreneurial opportunities for students. The success of a digital business does not only depend on how often social media is used, but also on how effectively it is utilized. This study adopts a quantitative approach. Data were collected through a survey involving 88 active FEBM UMRAH students who have a digital business. The data were analyzed using multiple linear regression with the SPSS version 26 software. The results show that both the use and effectiveness of social media significantly and positively influence students' satisfaction in digital business. This influence was proven to be strong when tested both partially and simultaneously. These findings have important implications. For educational institutions, it is recommended to enhance digital marketing training programs. For students, the results of this study can serve as a guide to optimize their use of social media for the advancement of their digital businesses.